CCD VRI photometry of the old open cluster NGC 7142 - Punanova, A.F.; Loktin, A.V.; Krushinsky, V.V.; Popov, A.A. (Advances in Astronomy and Space Physics, 2012)
Photometry of 2194 stars in the field of the open cluster NGC 7142 in VRI filters was performed to search variable stars. Eleven probable variable stars were found using robust median statistics. We separated probable cluster members using proper motions from UCAC3 and our photometric diagrams. Also we used our VRI photometry and JHK photometry from 2MASS to improve the age and the reddening for the cluster assuming the distance 1683 pc from WEBDA database.